Internet of things and its applications - Shanmukha Sai, Y; Kiran Kumar, K (International Journal of Engineering and Technology, 2018)
IOT is creating impeccable things by improving the performance of system in the field of communications in many technical applications in expedite manner and taken the system performance to next level. implementing IOT in today's world out do's the response time of the system to the normal system response in R&D applications. this paper depicts the challenges and the problems in various domains and gave the solution by imbibing IOT Technology by standardizing the system processes to meet the industrial as well as domestic needs.Â